KANTOWSKI-SACHS IN SAEZ –BALLESTER THEORY OF GRAVITATION WITH COLD DARK MATTER AND DARK ENERGY - A.NARASIMHA RAO, D.NEELIMA, Y.PRASANTHI, K.SURESH, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
In this study, we looked at the Kantowski- Sachs metric in the Saez-Ballester [1986] theory of gravitation filled with cold matter and dark energy. To arrive to a solution, we used a specific form of deceleration parameter presented by Singha and Debnath [2009]. There's also a discussion of the properties.